Coupling of single DBT molecules to a graphene monolayer: proof of principle for a graphene nanoruler. Issue 1728 (23rd February 2015) - Mazzamuto, G.; Tabani, A.; Pazzagli, S.; Rizvi, S.; Reserbat-Plantey, A.; Schädler, K.; Navickaite, G.; Gaudreau, L.; Cataliotti, F.S.; Koppens, F.; Toninelli, C.
ABSTRACT: We report on our recent progress in the study of single Dibenzoterrylene (DBT) molecules as single photon sources and nanoscale probes. We consider DBT molecules embedded in thin anthracene films, a system that allows stable single photon emission both at room and at cryogenic temperatures. We investigate the most important optical properties of the DBT:anthracene system as a whole. We then perform a full statistical study of the coupling between single DBT molecules by measuring the lifetimes of DBT both in the coupled and in the uncoupled case. The experimental results are framed into a simple universal scaling model, where the magnitude of coupling depends solely on universal parameters and on the distance d between the single emitter and the graphene monolayer. We apply this model to infer d and provide a proof of principle for a position ruler at the nanoscale [1].